Pengaruh Pajak, Multinasionalitas, Tunneling Insentive, dan Kepemilikan Asing Terhadap Transfer Pricing - Wati Epindi, Resna; Rahmi, Febri (Magister Ilmu Akuntansi Universitas Jambi, 2024)
This research aims to determine the influence of taxes, multinationality, tunneling incentive and foreign ownership on transfer pricing in LQ45 companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The method in this research uses quantitative methods. The hypothesis in this research was tested using panel data regression analysis with the Eviews 12 program. The sample for this research was obtained using the Purposive Sampling technique, so that a sample of 26 companies was obtained within 3 years and a total of 78 sample units were obtained. The results of this research show that partially the tax and tunneling incentive variables have an effect on transfer pricing, partially the foreign ownership variable has a negative effect on transfer pricing. Meanwhile, the multinationality variable has no effect on transfer pricing.